Bank Commitment to Ethics - Golja, Tea; . Krstinić – Nižić; ., Marinela (Information Management and Business Review, 2011)
This paper brings theoretical approach of ethics in financial industry as well as research results from Croatian banks. The role of ethics in financial industry becomes every day more important issue, also there are no more questions of ethics institutionalisation - it is a question of ethical behaviour. Research limitation was subject matter so sample was reduced to seven major banks in Croatia which are actively involved in creating ethical values. The paper implies stakeholders’ orientations which assure understanding, learning and improving organisation; as well as identification, development and implementation of appropriate strategy also larger attention in future should be given to institutionalisation of ethics, on every level, because main ethical dilemmas according to bank managers trace roots in society culture. The value of this paper is based on the uniqueness of the research results about ethics in Croatian banks.